2016
DOI: 10.1186/s40064-016-3408-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances in Japanese patients with inflammatory bowel disease and their impact on disease flare

Abstract: BackgroundSeveral studies have reported a significant association between sleep disturbance and inflammatory bowel disease (IBD). The aim of the present study is to compare the clinical characteristics and the health-related quality of life (HR-QOL) of Japanese IBD patients with or without sleep disturbances, and to investigate the risk factors for disease flare in these patients.MethodsIBD patients were asked to complete a self-administered questionnaire including the Pittsburg sleep quality index and the 8-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…However, the same effect was not demonstrated for patients with ulcerative colitis (UC) [ 16 ]. Similar results, but accounting for both CD and UC were also found in a study involving 177 Japanese patients, which demonstrated an increased risk for IBD flare within one year in patients with sleep disorders [ 17 ].…”
Section: Introductionsupporting
confidence: 81%
“…However, the same effect was not demonstrated for patients with ulcerative colitis (UC) [ 16 ]. Similar results, but accounting for both CD and UC were also found in a study involving 177 Japanese patients, which demonstrated an increased risk for IBD flare within one year in patients with sleep disorders [ 17 ].…”
Section: Introductionsupporting
confidence: 81%
“…This result was similar to those of previous studies. For example, Uemura et al reported the prevalence of sleep disturbances was 44.1% in Japanese IBD patients (23). In a study from China, 55.8% IBD patients reported poor sleep (16).…”
Section: Discussionmentioning
confidence: 99%
“…IBD are chronic inflammatory disorders of the intestine with unknown pathogenesis, including Crohn’s disease and ulcerative colitis. In a recent study, half of the IBD patients reported sleep disturbances as assessed by the PSQI (550), with strongest associations in patients with active disease (10, 209). Based on data from the Nurses’ Heath Survey with over 400 IBD cases, self-reported sleep duration of <6 h and >9 h per night increased risk of ulcerative colitis (11).…”
Section: The Sleep Response To Immune Activationmentioning
confidence: 99%